‘Magic Negro’, Saint or Comrade: Representations of Nelson Mandela in Film (Altre Modernità, 2014)
“In the late 1980s, Nelson Mandela stood alone against the apartheid state.” This comment taken from the DVD Box set cover of Nelson Mandela: From Freedom to History summarises the approach taken by many of the cinematic and televisual representations of Mandela. Linked with this is a statement by the CEO of Marriott which speaks of Mandela as “an individual who changed the arc of history through his or her singular contribution, not as a function of the era or the movement but because of what they did alone.” Together, these descriptions attempt to appropriate Mandela for a sanitised version of western individualism which sees him variously as a liberal icon, saintly hero, or the celebrity one-off “magic negro”, in Okwongo’s damning phrase taken from his magisterial valedictory piece “Mandela will never, ever be your minstrel” (Okwongo 2013). In the process, Mandela’s role in the anti-apartheid...